Reserve constrained dynamic optimal power flow subject to valve-point effects, prohibited zones and multi-fuel constraints - Niknam, Taher; Azizipanah-Abarghooee, Rasoul; Narimani, Mohammad Rasoul (Energy (Oxford), 2012)
This paper proposes a new method called the enhanced charged system search algorithm in order to solve the reserve constrained dynamic optimal power flow. The optimal power flow (OPF) is applied to develop the corrective strategies and to make the least cost dispatches. The static OPF solutions will usually result in unattractive generation cost in a dynamic environment, so to cope with this problem it is necessary to solve the dynamic optimal power flow which considers time-related constraints along with time-separated limits. Also, some restrictions such as prohibited operating zones and valve-point effects beside the multi-fuel type of generation units should be taken into account in order to get closer to the real condition of the power systems. Furthermore, to ensure secure real-time power system operations, the system operator must schedule sufficient resources to meet energy demand and operating reserve requirements, simultaneously. This problem is a complex optimization problem spontaneously which its complexity is increased with considering all above constraints. This paper utilizes an enhanced charged system search algorithm, which is a newly developed optimization algorithm, to solve the proposed problem. This algorithm is equipped with a novel mutation strategy in order to increase the population diversity and to amend the convergence criteria. For validating the ability of the proposed algorithm, it is applied to two small- and large-scale case studies including 30 and 118 buses test systems. ▸ Present a new method for reserve constrained dynamic OPF. ▸ Consider prohibited operating zones effect. ▸ Consider valve-point effects. ▸ Consider the multi-fuel type of generation unit. ▸ Consider the ramp rate of generation units.